The river is waiting : a novel [compact disc, unabridged] - Lamb, Wally (Simon & Schuster Audio, 2025)
Corby Ledbetter is struggling. New fatherhood, the loss of his job, and a growing secret addiction have thrown his marriage to his beloved Emily into a tailspin. And that's before he causes the tragedy that tears the family apart. Sentenced to prison, Corby struggles to survive life on the inside, where he bears witness to frightful acts of brutality but also experiences small acts of kindness and elemental kinship with a prison librarian who sees his light and some of his fellow offenders, including a tender-hearted cellmate and a troubled teen desperate for a role model. Buoyed by them and by his mother's enduring faith in him, Corby begins to transcend the boundaries of his confinement, sustained by his hope that mercy and reconciliation might still be possible. Can his crimes ever be forgiven by those he loves?